Technoeconomic Study of Belitung Kaolin as Import Substitution Material in Fiber Cement Board Production - nurhidayati nurhidayati; kristanto wahyudi; faiza elisa hasfianti (Balai Besar Keramik, 2020)
Cement board that commonly used as raw material for cheap housing component is calcium silicate cement board (fiber cement boards). However, the clay used as raw material for cement boards is still imported. In 2019, imported clay used for construction industry in Indonesia amounted to 57,000 tonnes per year with a transaction value of more than US 38 million. On the other hand, Indonesia, especially the province of Bangka Belitung, has a value of kaolin resources of 376,687,532 tons. Baristand Banjarbaru has successfully applied Belitung kaolin as a substitute for imported clay in cement board production. The physical properties of cement board made of kaolin Belitung were not significantly different from cement board made of imported clay.Therefore, Belitung kaolin has the potential to become a substitute for imported clay in cement board production and can be increased in terms of production scale so a techno-economic study is needed. Technoeconomic study had analyzed with the assumptions for a cement board production capacity of 100 tons / day, an investment age of 5 years, an initial investment of 0 for imported clay as raw material and 13,167,000,000 for kaolin as raw material or equivalent to 30% of sales. With the selling price of cement board Rp.55,000 / kg, the NPV of Belitung kaolin is 86,071,631,216.30 and the NPV of imported clay is 77,604,584,262.66. These results indicate that the cement board production business using Belitung kaolin as raw material is feasible to develop.